The Effectiveness of Jigsaw Techniques in Teaching Writing Analtical Exposition: (a quasi experimental study at the second year students of MA YUPPI Soreang) - Hidayat, Iip Sarip (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study was to test the effectiveness of the Jigsaw technique in teaching writing analytical exposition to second grade students at MA YUPPI Soreang. The research method was quasi experimental using an equivalent control group design. The results showed that the experimental group's mean score was 70.80 while the control group's mean score was 60.00. The standard deviation for experimental group is 6.581 and standard deviation for control group is 9.434 after data analysis. From a sample of 30 students, the degree of freedom (df) was Nx+Ny-2 = 28. And t-test for equality is 3.636. The researcher received a significance difference before and after treatment, after computation of data has completed. It means that employing the Jigsaw technique to teach writing analytical exposition text is beneficial